A mutagenesis screen for essential plastid biogenesis genes in human malaria parasites - Tang, Yong (PLoS Biol, 2019)
Endosymbiosis has driven major molecular and cellular innovations. Plasmodium spp. parasites that cause malaria contain an essential, non-photosynthetic plastid—the apicoplast—which originated from a secondary (eukaryote–eukaryote) endosymbiosis. To discover organellar pathways with evolutionary and biomedical significance, we performed a mutagenesis screen for essential genes required for apicoplast biogenesis in Plasmodium falciparum. Apicoplast(−) mutants were isolated using a chemical rescue that permits conditional disruption of the apicoplast and a new fluorescent reporter for organelle loss. Five candidate genes were validated (out of 12 identified), including a triosephosphate isomerase (TIM)-barrel protein that likely derived from a core metabolic enzyme but evolved a new activity. Our results demonstrate, to our knowledge, the first forward genetic screen to assign essential cellular functions to unannotated P. falciparum genes. A putative TIM-barrel enzyme and other newly identified apicoplast biogenesis proteins open opportunities to discover new mechanisms of organelle biogenesis, molecular evolution underlying eukaryotic diversity, and drug targets against multiple parasitic diseases.